DETEKSI DINI DAN EDUKASI MENGGUNAKAN APLIKASI IBU PINTAR STUNTING BAGI KADER DAN IBU BALITA - Utario, Yossy; Misniarti, Misniarti; Haryani, Sri (Poltekkes Kemenkes Bengkulu, 2025)
Education about stunting for cadres and mothers of toddlers is important to be carried out continuously as an effort to prevent stunting. The use of Android phones has become widespread in society. Offline or online applications are one of the effective educational media and can be used to increase knowledge about stunting. The Smart Mother Stunting Application can be used by cadres and mothers who have toddlers to find out how to detect stunting early and at the same time increase knowledge about stunting. This community service activity was carried out in July 2024 in the Fostered Village, namely Rimbo Recap Village, the working area of ​​the Watas Marga Health Center. This service activity aims to provide education to cadres and mothers of toddlers about stunting and how to detect stunting using the application. Socialization activities, providing education and simulation practices using the application for cadres and mothers of toddlers, as well as monitoring and evaluation. The data obtained showed an increase in the knowledge and skills of cadres and mothers about stunting and how to use the application using an Android phone. Early detection and education of stunting need to be carried out continuously to increase public awareness in preventing stunting.